Angiogenesis in hematologic malignancies - Möhler, Thomas; Ho, Anthony Dick; Goldschmidt, Hartmut; Barlogie, B. (Critical reviews in oncology, hematology, 2003)
Angiogenesis is defined as the formation of new capillaries from preexisting blood vessels and plays an important role in the progression of solid tumors. Recently a similar relationship has been described in several hematologic malignancies. Expression of the angiogenic peptides vascular endothelial growth factor (VEGF) and basic fibroblast growth factor correlates with clinical characteristics in leukemia and non-Hodgkin's-lymphoma and the serum/plasma concentrations serve as predictors of poor prognosis. Increased bone marrow microvessels in multiple myeloma (MM) are correlated with decreased overall survival. Thalidomide which has antiangiogenic effects and direct cytotoxic effects was found to be effective in MM, myelodysplastic syndrome and acute myeloid leukemia (AML). Preliminary data indicate activity of VEGF-tyrosine kinase inhibitors in AML. Clinical research is now aimed at testing antiangiogenic treatment strategies in several hematologic neoplasms as well as identifying the best candidate patients for specific approaches.
Gesehen am 10.12.2021